Conditions for application of asymptotic method to electromagnetic field analysis in the system of “a current loop-an electroconducting body” - Vasetskyi, Yuriy; Mazurenko, Iryna; Dziuba, Konstiantyn (Publishing House of Lviv Polytechnic National University, 2014)
A study of the conditions of application of an approximate method for analysis of a threedimensional pulse electromagnetic field with an arbitrary current loop, which is located near the flat surface of a conductive body, has been performed. It has been shown that each term of the asymtotic series is calculated with some accuracy, and therefore it has its own minimum cutoff frequency. An assessment of cutoff frequencies has been done and appropriate intervals from the pulse start have been obtained depending on the number of the series’ term and its chosen tolerable error. Проведено дослідження умов застосування наближеного методу розрахунку тривимірного імпульсного електромагнітного поля довільного контура зі струмом, розташованого поблизу плоскої поверхні електропровідного тіла. Показано, що кожний член асимтотичного розкладання обчислюється з певною похибкою, у зв’язку з чим він має власну мінімальну граничну частоту. Отримано оцінку гранічних частот та встановлено відповідні проміжки часу від початку імпульсу в залежності від номера члена ряду і обраної припустимої його похибки.
Умови застосування асимптотичного метода розрахунку електромагнітного поля в системі “струмовийконтур-електропровідне середовище”
Keywords: three-dimensional pulse electromagnetic field; induced current; arbitrary current loop; asymptotic method